INDEKS ATEROGENIK PLASMA PADA PASIEN SINDROMA KORONER AKUT DENGAN DIABETES MELITUS TIPE 2 - , Dhite Bayu Nugroho ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: The purpose of this study is to understand the difference of AIP between ACS patient with DM type 2 and non DM. The hypothesis is the AIP is higher in ACS patient with DM type 2 compared with that in non DM. Method: The design was a cross-sectional study conducted to ACS patients either with DM type 2 or non DM admitted in ICCU Dr. Sardjito General Hospital. Consecutive sampling was conducted. Inclusion criteria were (1) man and non pregnant patients > 30 years old, (2) ACS patient with DM type 2 and no DM (3) patient with complete lipid profile data including total cholesterol, cholesterol LDL, cholesterol HDL and trigyceride.. Patients consuming lipid lowering therapy within 4 weeks prior to hospital admission were excluded, patient with acute illnesses, renal failure, heart failure, cirrhosis, chronic inflammation, malignancies were excluded. The diagnosis of ACS was based on clinical criteria, ECG and cardiac enzyme measurement. Sample data were collected from medical records. The different level of AIP between groups was analyzed with Student T test, ANOVA and correlation. Multivariate analysis with multiple liniear regression to determine whether the difference was independent from other variables. A p value < 0,05 was considered significant. Result: The result showed from 195 study subjects, most were men with average age 60 years old. The AIP was significantly higher in ACS patient with DM typel 2 compared with that in non DM, marked by higher AIP level (0,62 Â± 0,29 dan 0,53 Â± 0,27, nilai p=0,00) In multivariate analysis the difference of AIP level was independent (p=0,000).